2015
DOI: 10.1097/qad.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-cell contact facilitates HIV transmission from lymphocytes to astrocytes via CXCR4

Abstract: Objectives HIV reservoir in the brain represents a major barrier for curing HIV infection. As the most abundant, long-lived cell type, astrocytes play a critical role in maintaining the reservoir; however the mechanism of infection remains unknown. Here, we determine how viral transmission occurs from HIV-infected lymphocytes to astrocytes by cell-to-cell contact. Design and methods Human astrocytes were exposed to HIV-infected lymphocytes and monitored by live-imaging, confocal microscopy, transmission and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 76 publications
(73 reference statements)
1
53
0
Order By: Relevance
“…Recent data from in vitro studies have suggested that astrocytes could be infected following cell‐to‐cell contacts with HIV‐1‐infected cells (Li et al, ; Luo and He, ). It has been proposed that the mechanism by which astrocytes get infected in vivo is most likely through physical contacts with virus‐infected lymphocytes and/or microglia/macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data from in vitro studies have suggested that astrocytes could be infected following cell‐to‐cell contacts with HIV‐1‐infected cells (Li et al, ; Luo and He, ). It has been proposed that the mechanism by which astrocytes get infected in vivo is most likely through physical contacts with virus‐infected lymphocytes and/or microglia/macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…First, endocytosis leads to a very inefficient infection mode due to degradation of most HIV‐1 particles in the endosomal apparatus (Chauhan et al, ; Hao and Lyman, ). Second, a more efficient mode of entry relies on cell‐to‐cell contacts through cocultivation with virus‐infected lymphocytes, which involves a CD4‐independent fusion of immature/budding virions via gp120‐CXCR4 interactions (Li et al, ; Luo and He, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the deleterious nonstructural HIV‐1 proteins expressed by infected astrocytes is Tat, which can be secreted (Fan & He, ), damages the BBB, promotes glutamate excitotoxicity and exacerbates neuroinflammation (reviewed in [Cisneros & Ghorpade, ]). Finally, astrocytes were shown to be capable of transmitting HIV to immune cells by cell‐to‐cell contact in co‐culture experiments (Li et al, ), suggesting that they also contribute to virus spread. For a more in‐depth discussion of the potential of astrocytes to form virus reservoirs and promote neurological damage to the brain and HAND, the reader is referred to selected reviews (Carroll & Brew, ; Gray, Brew, & Churchill, ; Li, Henderson, & Nath, ; Saylor et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CD4-independent viruses likely are strongly selected against in vivo (32,48,49). Nonetheless, although not strictly CD4 independent, HIVs and SIVs with the ability to utilize low levels of CD4 for entry are well described, and this phenotype has been proposed to contribute to the infection of macrophages and microglial cells, which exhibit a lower density of CD4 than T cells (32,(43)(44)(45)(50)(51)(52)(53)(54)(55)(56)(57). For one neuropathic SIV isolate, its ability to cause AIDS encephalopathy in macaques correlated with the infection of brain-derived endothelial cells that expressed CCR5 but not CD4 (58).…”
mentioning
confidence: 99%